2015
DOI: 10.3762/bjnano.6.165
|View full text |Cite
|
Sign up to set email alerts
|

The eNanoMapper database for nanomaterial safety information

Abstract: Summary Background: The NanoSafety Cluster, a cluster of projects funded by the European Commision, identified the need for a computational infrastructure for toxicological data management of engineered nanomaterials (ENMs). Ontologies, open standards, and interoperable designs were envisioned to empower a harmonized approach to European research in nanotechnology. This setting provides a number of opportunities and challenges in the representation of nanomaterials data and the integration of ENM information o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 57 publications
(68 reference statements)
0
72
0
Order By: Relevance
“…Efforts are ongoing to develop databases where toxicity data and PC properties are collected in one place, in order to improve data availability and enable investigations supporting grouping for readacross and development of in silico methods (Chen et al 2017). eNanoMapper (Jeliazkova et al 2015) is supporting read-across applications and in silico modeling, and the running project GRACIOUS is defining a grouping framework that takes more explicitly into account similarity.…”
Section: Addressing Similaritymentioning
confidence: 99%
“…Efforts are ongoing to develop databases where toxicity data and PC properties are collected in one place, in order to improve data availability and enable investigations supporting grouping for readacross and development of in silico methods (Chen et al 2017). eNanoMapper (Jeliazkova et al 2015) is supporting read-across applications and in silico modeling, and the running project GRACIOUS is defining a grouping framework that takes more explicitly into account similarity.…”
Section: Addressing Similaritymentioning
confidence: 99%
“…Toxicological studies have shown that TiO 2 nanoparticles (NPs) induce oxidative stress in cells resulting in immune response, inflammation, genotoxicity, and cell damage [ 21 ]. The researcher looked for a dataset in the search engine of four databases eNanoMapper [ 22 ], caNanoLab [ 23 ], ChEMBL [ 24 ], and NanoCommons [ 25 ] for data related to TiO 2 induced cytotoxicity, immunotoxicity, genotoxicity, or oxidative stress.…”
Section: Methodsmentioning
confidence: 99%
“…The API is REST-like. eNanoMapper separates the API design from the server implementation; AMBIT is one of the reference implementations of OpenTox services (Jeliazkova and Jeliazkova, 2011) and more recently eNanoMapper database (Jeliazkova et al, 2015), and on the server-side uses Apache’s Tomcat. The API implements user authentication and authorization.…”
Section: Current Practice For Data Integration In the Nanotechnology mentioning
confidence: 99%
“…The eNanoMapper server currently does not use other web services, besides being able to retrieve chemical structures from public databases (e.g. PubChem). The full details of the eNanoMapper API, including a description of the computational services implementation (which uses and integrates a variety of technologies and also reads and writes from/to data services) are published (Jeliazkova et al, 2015)(Chomenidis et al, 2017). …”
Section: Current Practice For Data Integration In the Nanotechnology mentioning
confidence: 99%